2018 IEEE/ASME International Conference on Advanced Intelligent Mechatronics (AIM) 2018
DOI: 10.1109/aim.2018.8452382
|View full text |Cite
|
Sign up to set email alerts
|

An Adaptive-Compliance Manipulator for Contact-Based Aerial Applications

Abstract: This paper presents simulation and airborne test results for a quadrotor equipped with an actively-variable compliance manipulator for contact interaction. Typical applications of this type of manipulator might include sensor placement operations and non-destructive testing. It is shown that through the use of the proposed manipulator, the force experienced at the end-effector can be adaptively controlled, and the effect of interactions on the aircraft itself minimised. Simulation and airborne results show a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…31,32,68,[78][79][80][81][82] • Parallel or serial structure: University of Twente, 70,83,84 ETH Zurich, 85 Lockheed Martin's Advanced Technology Lab, 86 and University of Malaga 87 use parallel manipulators; others are mostly serial structures. 9,11,31,32,[78][79][80][81][82] • Revolute or prismatic joint: Prismatic joint manipulators are used by University of Bologna, 88 University of the West of England, 89 and University of Twente. 90,91 Other manipulators are with revolute joints.…”
Section: Robotic Manipulatormentioning
confidence: 99%
“…31,32,68,[78][79][80][81][82] • Parallel or serial structure: University of Twente, 70,83,84 ETH Zurich, 85 Lockheed Martin's Advanced Technology Lab, 86 and University of Malaga 87 use parallel manipulators; others are mostly serial structures. 9,11,31,32,[78][79][80][81][82] • Revolute or prismatic joint: Prismatic joint manipulators are used by University of Bologna, 88 University of the West of England, 89 and University of Twente. 90,91 Other manipulators are with revolute joints.…”
Section: Robotic Manipulatormentioning
confidence: 99%
“…The proposed design consists of a single-DoF manipulator actuated by a prismatic joint. Amongst the improvements brought up from its previous version seen in [9] there is a more powerful on-board computer, i.e. Raspberry Pi 3 (1.4 GHz 64-bit quadcore ARM Cortex-A53 processor) with Wi-Fi connectivity and logging capabilities.…”
Section: Manipulator Designmentioning
confidence: 99%
“…Likewise, compliance is also a key feature in aerial manipulation thanks to the several advantages that it brings to the aerial system as a whole. Some of these advantages are energy absorbance in case of collision [2], force estimation and obstacle detection [24], and improved in-flight stability thanks to the dampening of perturbations [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…These control approaches demonstrate force estimation and motion feedback at the end-effector, improving stable contact during aerial interaction [4]- [7]. In our previous work [8], [9], compliance was introduced in the aerial system in the form of a variable-gain controller for the manipulator, while keeping a standalone flight controller on the aerial platform. Results demonstrated that by adapting the manipulator control gains, the dynamic response of the system as a whole changed and different output forces were generated at the end-effector, allowing us to fine-tune the overall compliant behaviour.…”
Section: Introductionmentioning
confidence: 99%